9x-.3=5.9-.2x

Simple and best practice solution for 9x-.3=5.9-.2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-.3=5.9-.2x equation:


Simplifying
9x + -0.3 = 5.9 + -0.2x

Reorder the terms:
-0.3 + 9x = 5.9 + -0.2x

Solving
-0.3 + 9x = 5.9 + -0.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.2x' to each side of the equation.
-0.3 + 9x + 0.2x = 5.9 + -0.2x + 0.2x

Combine like terms: 9x + 0.2x = 9.2x
-0.3 + 9.2x = 5.9 + -0.2x + 0.2x

Combine like terms: -0.2x + 0.2x = 0.0
-0.3 + 9.2x = 5.9 + 0.0
-0.3 + 9.2x = 5.9

Add '0.3' to each side of the equation.
-0.3 + 0.3 + 9.2x = 5.9 + 0.3

Combine like terms: -0.3 + 0.3 = 0.0
0.0 + 9.2x = 5.9 + 0.3
9.2x = 5.9 + 0.3

Combine like terms: 5.9 + 0.3 = 6.2
9.2x = 6.2

Divide each side by '9.2'.
x = 0.6739130435

Simplifying
x = 0.6739130435

See similar equations:

| 4+3c=25 | | 5-9x=85 | | -3m-5(3x+7)=0 | | 3x-(-y)=7 | | 16x^7/-4x^3 | | 16x=36-3x | | x^2-16/x^2-3x-4= | | 2=r/3-1 | | 15×1/3 | | 20+x=36-3x | | 5x+3y=316 | | 9x-3(-5x-2)=8x | | 1/8x=50 | | 12x+28=18x-20 | | (8x-8)1.5=64 | | -1=4(3-x*2) | | x+x*x+x*x*x= | | 2x-3(-3)-2=4 | | (4x-16)0.5=36 | | 2(x+1)=-3(3x-2) | | 6.666+x=12-x | | 6(10-7n)=-42-8n | | 2*(-9)*3=(-54) | | -46=-14-4x | | -12v=-13.4v-18.48 | | 15*0.3= | | 2(.25)+1/2(x-2)=0.4x | | -12=-13.4v-18.48 | | 9=3(7x+2) | | (x+y)(30x+32768x-x)= | | -13-2y=7-11y+11y | | .50X+50=100 |

Equations solver categories